(untitled) (Journal of Libya for geographical studies, 2022)
On international level, overfishing appeared in most of the world’s seas and oceans the Mediterranean Sea, for instance, due to the increasing population and the technological advancement of fishing equipment and fleets. Overfishing spread in the Mediterranean Sea and its impact became apparent represented in causing exposure of fish reserves to deterioration risks. Libya possesses a coastal line on the Mediterranean Sea. The northwestern coasts are deemed the most prominent areas experiencing unbalanced overfishing due fishermen’s inconsideration to appropriate fishing seasons in addition to their use of illegal fishing nets and manual explosives. The present study adopted several approaches; mainly analytical and subjective approaches and in term of methodologies, cartographic method was applied to visualize the data on maps using geographic information system program (Arc.GIS 10.2) in addition to interviews and field visits. The study concluded several results mainly that overfishing in northwestern coasts of Libya has not only impacted the reservoir of marine biology but also the biological diversity as a deterioration became visible in the reserves of several types of fish such as deep water fish as the ( Dusky Groper) and surface fish such as the ( Blue Fin Tuna) moreover the negative impacts it has on other marine biology such as sea turtles and birds that have been exposed to the risk of extinction. The extinction of some types of marine biology will lead to disorder in the environmental balance such as the spread of the poisonous jellyfish due to the overfishing of the angel shark in the coasts of the study area. In order to address overfishing, the study recommended making efforts to assisting fishermen in terms of providing them with financial aids through fishing associations’ funding; furthermore, working on enacting the relevant laws to marine resources protection and the extensive cooperation between the governmental entities such as Ministry of Environment, Ministry of Marine Resources and Ministry of Planning, and research centers and universities.